Orchidaceae occurring in white-sand ecosystems of the Uatumã Sustainable Development Reserve in Central Amazon - Klein, Viviane Pagnussat; Piedade, Maria Teresa Fernandez (Phytotaxa, 2019)
We studied the Orchidaceae flora of white-sand ecosystems (campinaranas) in the Uatumã Sustainable Development Reserve, Amazonas State, Brazil. The family was represented by 60 species and 31 genera, with Maxillaria (10 spp.), Epidendrum (9 spp.) and Octomeria (6 spp.) being the most rich genera. Among the listed species, approximately 40% have a restricted distribution in the Amazonian domain, ocurring in different ecosystems. Four species, Cattleya wallisii, Maxillaria brasiliensis, Octomeria sagittata and Prosthechea vespa are known only from Brazil. Epiphytism was the most common habit, and Aldina heterophylla (Fabaceae) was the preferential phorophyte, with 67% of the total taxa occurring associated with this tree species. Taxonomic descriptions, illustrations, ecological comments, phenological information, geographical distribution and an identification key of the taxa are provided.